High-Performance Organic Solar Cells Based on a Small Molecule with Alkylthio-Thienyl-Conjugated Side Chains without Extra Treatments - Cui, Chaohua; Guo, Xia; Min, Jie; Guo, Bing; Cheng, Xiao; Zhang, Maojie; Brabec, Christoph; Li, Yongfang (Advanced Materials, 2015)
A new 2D-conjugated small molecule with alkylthio-thienyl-conjugated side chains (BDTT-S-TR) is synthesized for application as a donor material in organic solar cells (OSCs). The OSCs based on BDTT-S-TR/PCBM demonstrate a power conversion efficiency (PCE) of 9.20% without extra treatment. Moreover, an encouraging PCE of 6.68% is achieved from the device with active area of 144 mm.
Keywords: conjugated side chains; organic molecules; organic solar cells; solution processability